Digital Transformation in Logistics Companies and Its Impact on Human Resources Marketing Strategies and Competition in International Trade - Nurmin Arianto; Kasmad Kasmad; Lia Asmalah; Windy Gustia Wardani (Jurnal Manajemen Industri dan Logistik, 2025)
This study aims to analyze Digital Transformation in Logistics Companies and Its Impact on Human Resources, Marketing Strategy, and Competition in International Trade. This study uses a quantitative method with a descriptive and explanatory approach. survey research method. The data analysis technique for this study uses statistical analysis using the Smart PLS (Partial Least Square) 3.0 program. The population and sample in this study are logistics companies that have implemented digital transformation, both nationally and internationally, the technique used in this study is purposive sampling. The results of the study show that, 1) Digital Transformation in logistics companies has an impact on HR in international trade, 2) Digital Transformation of logistics companies does not have an impact on marketing strategies in international trade, 3) Digital Transformation of logistics companies does not have an impact on competition in international trade.